2002
DOI: 10.1088/0022-3727/35/20/314
|View full text |Cite
|
Sign up to set email alerts
|

The role of negative ions in the propagation of discharges across insulating surfaces

Abstract: The relative importance of atmospheric negative ions in corona formation and breakdown in a radial electric field has been investigated, with special reference to effects occurring at an insulating surface of a cycloaliphatic polyurethane with dolomite filler. The inception times, corona charge, light emission (by UV photography) and sparkover voltages under lightning impulses have been recorded under natural atmospheric conditions and under the influence of negative ions introduced from an auxiliary corona. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 11 publications
0
14
0
1
Order By: Relevance
“…However when discharge is taking place over a gas/insulator interface results from previous investigations have shown that the critical volume as typically defined in air is not well appropriate to describe the conditions of streamer inception [36]. Moreover based on this present work, our camera recordings revealed that corona streamers on ice surface can be initiated midway of the surface, far from the HV rod electrode, as illustrated in Figure 5b.…”
Section: Streamer Inceptionmentioning
confidence: 56%
“…However when discharge is taking place over a gas/insulator interface results from previous investigations have shown that the critical volume as typically defined in air is not well appropriate to describe the conditions of streamer inception [36]. Moreover based on this present work, our camera recordings revealed that corona streamers on ice surface can be initiated midway of the surface, far from the HV rod electrode, as illustrated in Figure 5b.…”
Section: Streamer Inceptionmentioning
confidence: 56%
“…The relative importance of atmospheric negative ions in corona formation and breakdown has been investigated many times (see, e.g. [32]). As already mentioned, the main negatively charged species in cold air plasmas is O − 2 , but only free electrons play a role in streamer propagation.…”
Section: Process Of Fast Electron Detachmentmentioning
confidence: 99%
“…In addition, several mechanisms have been advanced to explain the mechanisms implicated in their initiation and development. Among these mechanisms the dynamic interaction between the discharge and the insulator surface [5 -7], the accumulation of electrical charge at the insulator surface [8][9][10][11][12][13][14], the modification of the ionisation and attachment coefficient [15,16] and the distortion of electric field [17,18]. Therefore the understanding of the initiation conditions of creeping discharges and the parameters characterising their development up to breakdown or flashover is very helpful for the design and the dimensioning of high-voltage components and systems (bushings, insulators, switchgears, gas insulating lines, gas circuit breaker .…”
Section: Introductionmentioning
confidence: 99%